Distributed event-triggered affine formation control for multiple underactuated marine surface vehicles. (1st December 2022) - Zheng, Yuxin; Zhang, Lei; Huang, Bing; Su, Yumin
Abstract: This article focuses on the distributed event-triggered affine formation control problem for multiple underactuated marine surface vehicles (UMSVs) considering affine transformation and communication energy consumption under a directed interaction topology. Firstly, the affine transformation mechanism is adopted to improve the flexibility and maneuverability of the formation. The proposed technique allows a rich collection of collective motions such as translation, rotation, scaling, and the combination of these transformations. Then, unlike the event-triggered control of a single marine vehicle, this paper considers reducing communication frequency between vehicles. Thus, an event-triggered mechanism is proposed, which can save computation resources compared with traditional ones while excluding the Zeno behavior. Subsequently, it is proved that all signals in the closed-loop system are ultimately uniformly bounded (UUB), meanwhile, all tracking errors converge to a small compact set under the proposed control strategy. Finally, numerical simulations illustrate the effectiveness of the proposed formation controller. Highlights: A distributed event-triggered affine formation control algorithm is developed to solve the trajectory tracking problem for UMSVs formation. A novel affine transformation mechanism is devised to enables UMSVs to move as a group in formation translation, shearing, rotation and scaling maneuvers. An event-triggered scheme is designed to update the measurement signal so as to save the communication resource.